Land Use Changes and the Corresponding Ecological Risks - Song, Wei; Xie, Hualin (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on land use change processes and their driving mechanisms, ecological risks and eco-environmental effects. The spatio-temporal pattern changes and key driving factors of cultivated land, urban land, wetland, ecological land and mining land were studied at national or regional scales, such as in China, the Tibetan Plateau, the Yangtze River Delta, the Yellow River Basin, urban agglomeration and mountainous areas. The economic or ecological efficiency, ecological risks and environmental effects of typical land use changes, e.g., the effects of ecological restoration on critical services, the impact of planting structure changes on water resources and the impacts of urban expansion on food security and air pollution, as well as the environmental risks of chemical fertilizer application and coal-mining, were analyzed in depth using multi-source data and multiple methods. Revealing land use change characteristics and their potential ecological risks and impacts on food security, ecosystem services and climate change is an important basis for the sustainable development of social economies and ecosystems. The scientific methodologies, analyzed findings, systematic insights, and policy implications of this reprint will contribute to the advancement of knowledge and provide practical guidance for sustainable land management and land optimization to improve human wellbeing and eco-environment quality.